THE IMPACT OF RETURN ON PROFIT, COMPANY VALUE AND COMPANY SIZE ON STOCK PRICES IN MANUFACTURING COMPANIES LISTED ON IDX - Junus, Amiruddin; Darmawati , Darmawati; Warkula, Yohanes Zefnath (jfpublisher, 2022)
This study aims to examine and analyze the impact of earnings returns, firm value, and firm size on stock prices in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The populations in this study are manufacturing companies listed on the Indonesia Stock Exchange according to the publication of the Indonesia Stock Exchange (IDX). The companies that are the sample of this research are manufacturing companies in the various industrial sectors that have been listed on the IDX since the data for the period in this study is 2018-2020, 54 manufacturing companies in the various industries were selected. The results showed that the return on earnings had a positive effect on stock prices, while firm value and firm size had no effect on stock prices in manufacturing companies in the various industrial sectors.